Determinant Analysis of Electronic Medical Record Completeness Based on Physician Workload: A Systematic Literature Review - Aditya Ihza Dwi Pangestu; Muzakar Isa; Noor Alis Setiyadi (Journal La Medihealtico, 2026)
Electronic Health Records (EHR) are crucial tools in the transformation of clinical governance and hospital information management. Despite offering numerous benefits, EHR implementation often conflicts with physicians’ heavy clinical workload, which risks reducing the level of documentation compliance and completeness. This incomplete medical data not only threatens patient safety but also hinders the insurance claims process and harms institutional operations. This study aims to systematically identify and analyze the factors determining EHR documentation completeness based on physician workload in inpatient facilities. The method used is a Systematic Literature Review (SLR) following the PRISMA 2020 framework. A comprehensive literature search was conducted using the Google Scholar database, focusing on publications from 2021 to 2026. From the initial identification to the final screening stage, 18 empirical study articles that met all inclusion criteria were extracted and analyzed thematically. The results of the literature review indicate that high operational burdens affect EHR completeness through two main determinant dimensions. First, the heavy workload during service hours triggers documentation delays, forcing physicians to perform additional administrative work outside of official duty hours (pajama time), resulting in reduced data accuracy. Second, the cognitive burden stemming from non-ergonomic EHR system interface designs leads to digital interaction fatigue (click fatigue) among medical personnel. In conclusion, excessive clinical and administrative workloads have been shown to significantly reduce the compliance rate for complete EHR documentation. Consequently, hospital management is advised to redesign system interfaces to better align with clinical workflows and provide support such as documentation assistants to optimize medical record quality without compromising physician well-being.